Genocidas ir rezistencija Nr. 45(1) - Grickevičius, Artūras; Rukšėnas, Alfredas; Pocius, Mindaugas; Burinskaitė, Kristina; Indrišionis, Darius; Jasiewicz, Krzysztof; Sereičikas, Mindaugas (Genocidas ir rezistencija, 2019)
Pilnas leidinys